Factors associated with the evolution of COVID-19 in pregnant women: a Brazilian population-based study - Andrade, Luis Henrique de [UNESP]; Santos, Gustavo Gonçalves Dos; Sordi, Mônica Aparecida de Paula de [UNESP]; Nunes, Hélio Rubens de Carvalho [UNESP]; Parada, Cristina Maria Garcia de Lima [UNESP] (FapUNIFESP (SciELO), 2023)
OBJECTIVE: To assess the evolution of COVID-19 among Brazilian pregnant women, identifying sociodemographic and clinical predictors related to admission to ICU - Intensive Care Unit and death. METHOD: Cross-sectional, population-based study, carried out with a secondary database, based on data from the Influenza Epidemiological Surveillance Information System. Descriptive analysis was performed, followed by multiple linear regression with Poisson response, adopting critical p < 0.05. RESULTS: Intensive care admission rates of 28.2% and death rates of 9.5% were identified. Region of residence, gestational trimester, number of comorbidities and respiratory signs and symptoms were associated with the risk of admission to intensive care. Age over 34 years, comorbidities, oxygen saturation equal to or less than 95%, admission to intensive care and ventilatory support, invasive or not, increased the risk of death. CONCLUSION: Sociodemographic and clinical predictors showed an association with hospitalization in intensive care and death of pregnant women with COVID-19.